Hepatitis B control among children in the Eastern Mediterranean Region of the World Health Organization. Issue 21 (5th May 2016) - Allison, Robert D.; Teleb, Nadia; Al Awaidy, Salah; Ashmony, Hossam; Alexander, James P.; Patel, Minal K.
Abstract: In the pre-vaccination era, the prevalence of chronic hepatitis B virus (HBV) infection in the World Health Organization (WHO) Eastern Mediterranean Region (EMR) ranged from two to seven percent in a total population of over 580 million people. Mortality estimates place cirrhosis among the top ten causes of years of life lost in the EMR. The region has made notable achievements, improving coverage from only 6% in 1992, when WHO recommended hepatitis B vaccination of all infants, to 83% in 2014. Member states adopted a hepatitis B control target in 2009 to reduce chronic hepatitis B virus infection prevalence to less than one percent among children aged <5 years by 2015. This report reviews progress toward achievement, challenges faced, and the next steps forward of hepatitis B control among children in the EMR.